Study of Local Duck Rations from Colocasia Esculenta Flour on Egg Production and Cholesterol Content - Zasmeli Suhaemi; Sari Gando Hayati (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
Colocasia esculenta is the plants feed ingredients shown to reduce the cholesterol content of livestock products, such as in ducks. This study aims to examine the use of Colocasia esculenta Scho. plant in local duck rations on egg production, and the content of cholesterol and triglycerides. As a treatment in this study were the level of use of Colocasia esculenta meal (CM), 0%, 5%, 10%, 15% and 20%, with 4 replications, which designed with a completely randomized design. As many as 80 ducks in the laying period were used, ranging in age from 19 to 30 weeks. The data obtained showed that an increasing level of CM up to 10% resulted in increased egg production, egg weight and decreased feed convertion ratio. Conversely, the blood and yolk total cholesterol and triglyceride content actually decreased until the level CM was 20%. It was concluded that the use of CM up to a level of 10% could improve the performance of egg production, and the use of up to a level of 20% decreased the cholesterol and triglyceride content of blood and egg yolk. This is an important role about those subject for required healthy food for human nutrition